2015
DOI: 10.1038/eye.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

Failure of intravitreal bevacizumab in the treatment of choroidal metastasis

Abstract: Background Metastasis to choroid is the most common intraocular malignancy, arising most frequently from carcinoma of breast in women and lung in men. Recent case reports have described successful use of intravitreal bevacizumab to achieve local control of such tumours. Materials and methods Five cases of choroidal metastases from varying primaries: breast, lung, and colon were treated with intravitreal bevacizumab, and tumour response observed and documented with serial photographs and B-scans. Results Four o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…In 2 cases of SCLC, intravitreal bevacizumab was not effective, but it improved choroidal metastasis in 7 of 9 NSCLC cases. Intravitreal bevacizumab is a promising alternative to ocular radiation, especially for treatment of non-small non-squamous lung cancer [ 1 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2 cases of SCLC, intravitreal bevacizumab was not effective, but it improved choroidal metastasis in 7 of 9 NSCLC cases. Intravitreal bevacizumab is a promising alternative to ocular radiation, especially for treatment of non-small non-squamous lung cancer [ 1 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, if it is used with intravitreal injection, high-dose bevacizumab can cure the metastasis lesions [ 6 , 9 ]. To date, 9 reports involving 11 cases have been published on intravitreal bevacizumab as a primary treatment modality for choroidal metastasis from lung cancer [ 1 , 10 , 11 ]. Herein, we report a case of effective treatment with intravitreal injection of Bevacizumab for exudative retinal detachment secondary to choroidal metastasis of non-small cell carcinoma (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
“…Papers such as those published by Ma et al, Ha et al, Khawaja et al, and Lin et al showed unilateral single choroidal mass in reports of colorectal adenocarcinoma [5,13,19,32]. Moreover, Maudgil et al described two eyes with a single choroidal mass in patients with diagnosis of adenocarcinoma of the cecum, while Ward et al reported single bilateral choroidal masses in a patient with presumed colon cancer [33,34]. Similar to most previous publications, our patient presented with a unilateral hyperreflective and hyperechogenic choroidal mass in the inferior temporal arcade.…”
Section: Main Textmentioning
confidence: 99%
“…We read with interest the article published in your journal 'Failure of intravitreal bevacizumab in the treatment of choroidal metastasis'. 1 We agree that intravitreal bevacizumab as the primary treatment of choroidal metastases might not always be efficacious in controlling the disease and should not delay treatment that is more radical.…”
Section: Conflict Of Interestmentioning
confidence: 99%